Jatīẏa Mahilā Sammelana, 1979 (Bāṃlādeśa Jātīẏa Mahilā Saṃsthāra Kāryakarī Parishada, 1981)
Proceedings of the National Women's Conference, Bangladesh, 1975; conprises papers on socioeconomic and political condition of women in Bangladesh.